A3.7 Comparison of the Effects of Th17 and Th1 Cells on Endothelial Cells and Synoviocytes. (25th February 2013) - Hot, Arnaud; Maggi, Laura; Lavocat, Fabien; Annunziato, Francesco; Miossec, Pierre
Abstract : Background: Interaction between different types of T-cells and surrounding non-hematopoietic cells is essential for the proper function of the immune system. Here, we focus on the synoviocytes from RA patients and Endothelial Cells (EC) and compare their interaction with Th1 and Th17 cells. Methods: To assess the interaction of T cells with stromal cells, the effects of Th1 or Th17 cytokines, Th1 or Th17 clone supernatants and coculture of Th clones and stromal cells were analysed. HUVEC (Human Umbilical Vein Endothelial Cells) were used as a model for EC and synoviocytes were isolated from synovium from RA patients. CD4 + T cells, derived from PBMCs of healthy donors, were used to obtain T-cell clones. CD4 + T-cell clones were classified on the basis of their ability to produce IFN-γ and/or IL-17. T cell clones were polyclonally stimulated with anti-CD3/CD28. Cytokine expression was assessed with RT-PCR and production in supernatants by ELISA. Results: As previously described, IL-17A and TNF-α had a synergistic effect for both cells. Moreover, a stronger induction for IL-6 pro- duction was seen for synoviocytes compared to EC (1005 ± 22 pg/ml versus 250 ± 15 ng/ml respectively). Supernatants from inactivated Th1 or Th17 clones had no effect on EC. Regarding synoviocytes, supernatants from inactivated clones induced IL-6 and IL-8 mRNA with a stronger effect for Th17 cells (1000 fold versus 100 fold compared to resting synoviocytes, p = 0.045). While activated Th1 supernatants had a strong effect on EC and increased the expression of IL-6, IL-8, E-selectin, and tissue factor mRNA (98.12, 89 fold respectively, compare to control), Th17 supernatants had no effect. Activated Th1 and Th17 supernatants had the same effect on synoviocytes (254 and 754 fold compared to control). Th1 cells were more potent inducers of IL-6, IL-8 and tissue factor mRNA in EC than Th17 which had no significant effect (5, 12.5, 7.5 fold respectively compared to control). Th17 cells were most effective to stimulate IL-6 and IL-8 mRNA expression in synoviocytes compared to Th1 (100 fold versus 24 for IL-6 mRNA, p = 0.027). Anti-IL-17 antibody reduced IL-6 production from 20.0 ± 4.5 ng/mL to 13.2 ± 3.9 ng/ml (p = 0.032) in synoviocytes cultured with Th17 clones. Conclusions: While Th1 cells were able to induce inflammatory cytokine expression in EC and synoviocytes, Th17 cells were only active to promote inflammation in inflammatory cells such as synoviocytes. The effect of Th17 cells appears to depend of IL-17 and the type of stromal cells.